Autoantibodies Against the Immunodominant Bullous Pemphigoid Epitopes Are Rare in Patients With Dermatitis Herpetiformis and Coeliac Disease - Nätynki, Antti; Tuusa, Jussi; Hervonen, Kaisa; Kaukinen, Katri; Lindgren, Outi; Huilaja, Laura; Kokkonen, Nina; Salmi, Teea; Tasanen, Kaisa (Frontiers in Immunology, 2020)
Dermatitis herpetiformis (DH) is an extraintestinal manifestation of coeliac disease (CD). Patients with DH have an elevated risk of development of another autoimmune blistering skin disease, bullous pemphigoid (BP). In this study we investigated whether patients with DH and CD (mean age for both 49 years) have circulating autoantibodies against BP180, the major BP autoantigen. ELISA tests showed that only a few DH (3/46) and CD (2/43) patients had BP180-NC16A IgG autoantibodies. Immunoblotting found that more than half of the DH samples contained IgG autoantibodies against full-length BP180. Epitope mapping with 13 fusion proteins covering the BP180 polypeptide revealed that in DH and CD patients, IgG autoantibodies did not target the NC16A or other epitopes typical of BP but recognized other intracellular and mid-extracellular regions of BP180. None of the analyzed DH and CD patients with either ELISA or immunoblotting positivity had IgG or IgA reactivity against the cutaneous basement membrane in indirect immunofluorescence analysis or skin symptoms characteristic of BP. Although only a minority of middle-aged DH patients had IgG autoantibodies against the immunodominant epitopes of BP180, our results do not exclude the possibility that intermolecular epitope spreading could explain the switch from DH to BP in elderly patients